The Relationship of Disease-Specific Knowledge and Health Literacy With the Uptake of Self-Care Behaviors in CKD - Schrauben, Sarah J. (Kidney Int Rep, 2019)
INTRODUCTION: Individuals with chronic kidney disease (CKD) generally have poor participation in self-care. We hypothesized that greater kidney disease knowledge and health literacy would associate with better self-care. METHODS: We enrolled 401 participants with non–dialysis-dependent CKD from one academic center in this cross-sectional study. Validated surveys were used to assess health literacy level (inadequate vs. adequate; Rapid Estimate of Adult Literacy in Medicine), perceived kidney disease knowledge (Perceived Kidney Disease Knowledge Survey [PiKS]), objective kidney disease knowledge (Kidney Disease Knowledge Survey [KiKS]), and a CKD self-care measure was constructed as the sum of self-reported self-care behaviors using the adapted Summary of Diabetes Self-Care Activities Assessment. The association between health literacy level, PiKS scores, KiKS scores, and the CKD self-care measure was assessed with multivariable adjusted linear regression models. RESULTS: Participants had a mean age of 57 years and 17.7% had inadequate health literacy. PiKS scores were positively associated with the CKD self-care measure (β = 1.05, 95% confidence interval [CI] 0.50–1.63), and a positive trend was observed for KiKS scores and the CKD self-care measure (β = 0.30, 95% CI: −0.12 to 0.72). Health literacy was not associated with CKD self-care measure. CONCLUSION: Objective kidney disease knowledge is likely necessary, but not sufficient for self-care and may depend on the level of health literacy. Perceived kidney knowledge may offer a novel target to assess patients at risk for poor self-care, and be used in targeted educational interventions.